PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN ONLINE PADA LAZADA, PADA PENGGUNA LAZADA DI DAERAH JAKARTA TIMUR - P., Reza Syahdewo; Gunadi, Wasis (Feb Universitas Dirgantara Marsekal Suryadarma, 2020)
Research aims to determine if the quality of service and consumer confidence affect the Onlinepurchase decision on Lazada in East Jakarta, From the population consisting of users of Lazada both in EastJakarta area especially in the area Halim Perdanakusuma, Cijantung, Kampong Makasar, and LubangBuaya, taken samples consisting of 97 respondents.The method of analysis used is a quantitative descriptive method, namely by collecting primary andsecondary data to obtain the necessary statistical values, hereinafter drawn conclusions through partial andsimultaneous hypothesis testing of multiple linear regression. The result of this research is that the influenceof independent variables against dependent variables is indicated by a regression equation: Y = 1,972 +0.075 X1 + 0.384 X2, where Y = Online Purchase Decision on Lazada, X1 = Service Quality, and X2 =Consumer Confidence, where Î± = 5%: Quality of service partially does not affect the online purchasedecision on Lazada. This is demonstrated by the test statistical value: t-count = 1,736 < t-table = 1.98522, andor sig = 0.85 > Î± = 0.05. The consumer confidence in a partial has a significant effect on the onlinepurchase decision on Lazada. This is demonstrated by the statistical value of the test: t-count = 6,909 > T-table = 1,986, and or sig = 0.000 > 0.05. The quality of service and consumer confidence jointly has a significanteffect on the online buying decision on Lazada. This is demonstrated by the test statistical value: Fcount =177,508 > Ftable = 2.36, and or sig = 0.00 < 0.05.The coefficient of determination (R2) test indicates that R2is 0.786 which means that 78.6% data ofservice quality and consumer confidence variables can explain the online purchase decision variable, whilethe the remaining 21.4% is explained by other factors not addressed in this study.Keywords: Quality of service, consumer confidence, purchase decision.